Francisella Subverts Innate Immune Signaling: Focus On PI3K/Akt - Cremer, Thomas J.; Butchar, Jonathan P.; Tridandapani, Susheela (Frontiers in Microbiology, 2011)
Intracellular bacterial pathogens exploit host cells as a part of their lifecycle, and they do so by manipulating host cell signaling events. Many such bacteria are known to produce effector proteins that promote cell invasion, alter membrane trafficking and disrupt signaling cascades. This review highlights recent advances in our understanding of signaling pathways involved in host cell responses to Francisella tularensis, a facultative Gram-negative intracellular pathogen that causes tularemia. We highlight several key pathways that are targeted by Francisella, with a focus on the PI3K/Akt pathway. Lastly, we discuss the emerging role of microRNAs, specifically miR-155, as a key regulator of host signaling and defense.